Q: Factor the polynomial x 2 - 6 x plus 9?

Write your answer...

Submit

Related questions

2(x + 6)(x + 6) or 2(x + 6)2

(x-2)(x-3)

-2 and -6

Take out the common factor, 3: 3x + 6 = 3(x + 2).

n^2(n + 6)(n^2 - 6n + 36)

It is: (x+1)(x+6) when factored

(x + 6)(x + 2)

(5x - 1)(x + 6)

First divide by 6: 6(x2 - 3x + 2) = 6(x - 1)(x - 2)

(x+6)(X+20)

5x2 + 16x + 12 = (5x + 6)(x + 2)

2(4m-3)

2(4x - 3)

5x2 + 29x - 6 = (5x - 1)(x + 6).

(x - 3)(x + 6)

5x2-16x+12 = (5x-6)(x-2) when factored

(x - 6)(x - 3)

That doesn't factor neatly. Applying the quadratic formula, we find two real solutions:-6 plus or minus 2 times the square root of 2 x = -3.1715728752538097 x = -8.82842712474619

Yes.

(x - 6)(x - 9)

x2 - 9x + 18 = (x - 3)(x - 6)

-6 Check: -6+4-6+8 = 0

3(7x-6)

x+11x+30(x+5)(x+6)

2(x^2 +2x + 3)

Study guides